A Wolf in Sheep's Clothing: Reuse of Routinely Obtained Laboratory Data in Research - L Malin Overmars; Michael S A Niemantsverdriet; T Katrien J Groenhof; Mark C H De Groot; Cornelia A R Hulsbergen-Veelken; Wouter W Van Solinge; Ruben E A Musson; Maarten J Ten Berg; Imo E Hoefer; Saskia Haitjema (JMIR Publications, 2022)
Electronic health records (EHRs) contain valuable data for reuse in science, quality evaluations, and clinical decision support. Because routinely obtained laboratory data are abundantly present, often numeric, generated by certified laboratories, and stored in a structured way, one may assume that they are immediately fit for (re)use in research. However, behind each test result lies an extensive context of choices and considerations, made by both humans and machines, that introduces hidden patterns in the data. If they are unaware, researchers reusing routine laboratory data may eventually draw incorrect conclusions. In this paper, after discussing health care system characteristics on both the macro and micro level, we introduce the reader to hidden aspects of generating structured routine laboratory data in 4 steps (ordering, preanalysis, analysis, and postanalysis) and explain how each of these steps may interfere with the reuse of routine laboratory data. As researchers reusing these data, we underline the importance of domain knowledge of the health care professional, laboratory specialist, data manager, and patient to turn routine laboratory data into meaningful data sets to help obtain relevant insights that create value for clinical care.